Pentingnya Storytrlling Dalam Strategi Content Marketing - Angga Yudha Pratama; Hendra Riofita (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the extent of content marketing using storytelling. This study uses a qualitative research type with a netnography approach. with the creation of effective content marketing and storytelling to increase sales and even create awareness of the products being sold. Social media is the main media for implementing content marketing and storytelling strategies because of its speed in disseminating information. Marketing communication with social media can reach a wider target market. The use of content marketing and storytelling can increase sales as seen from the development of stores and the addition of branches.